Pengaruh Gaya Kepemimpinan Transformasional Dan Kompetensi Digital Pegawai Terhadap Produktivitas Pegawai Melalui Self-Efficacy Sebagai Variabel Intervening Pada Rumah Sakit Jiwa Prof. Dr. HB. Saanin Padang - Dira Fathimah Zahara; Vicky Brama Kumbara; Chintya Ones Charli (GLOBAL SCIENTS PUBLISHER, 2026)
This study aims to analyze the effect of recruitment and work experience on job performance with job placement as an intervening variable at PT. Pasoka Sumber Karya Padang. The study employed a quantitative explanatory research design with 65 respondents using census sampling. Data were analyzed using Structural Equation Modeling based on Partial Least Square (SEM-PLS). The findings indicate that recruitment and work experience significantly affect job performance. Both variables also significantly influence job placement. Job placement significantly affects job performance and mediates the relationship between recruitment, work experience, and job performance. The R² value of 0.71 indicates a strong explanatory model.